Thyroid and Glucocorticoid Hormones Promote Functional T-Tubule Development in Human-Induced Pluripotent Stem Cell–Derived Cardiomyocytes. Issue 12 (8th December 2017) - Parikh, Shan S.; Blackwell, Daniel J.; Gomez-Hurtado, Nieves; Frisk, Michael; Wang, Lili; Kim, Kyungsoo; Dahl, Christen P.; Fiane, Arnt; Tønnessen, Theis; Kryshtal, Dmytro O.; Louch, William E.; Knollmann, Bjorn C.
Abstract : Rationale: : Human-induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CM) are increasingly being used for modeling heart disease and are under development for regeneration of the injured heart. However, incomplete structural and functional maturation of hiPSC-CM, including lack of T-tubules, immature excitation–contraction coupling, and inefficient Ca-induced Ca release remain major limitations. Objective: : Thyroid and glucocorticoid hormones are critical for heart maturation. We hypothesized that their addition to standard protocols would promote T-tubule development and mature excitation–contraction coupling of hiPSC-CM when cultured on extracellular matrix with physiological stiffness (Matrigel mattress). Methods and Results: : hiPSC-CM were generated using a standard chemical differentiation method supplemented with T3 (triiodothyronine) and/or Dex (dexamethasone) during days 16 to 30 followed by single-cell culture for 5 days on Matrigel mattress. hiPSC-CM treated with T3+Dex, but not with either T3 or Dex alone, developed an extensive T-tubule network. Notably, Matrigel mattress was necessary for T-tubule formation. Compared with adult human ventricular cardiomyocytes, T-tubules in T3+Dex-treated hiPSC-CM were less organized and had more longitudinal elements. Confocal line scans demonstrated spatially and temporally uniform Ca release that is characteristic of excitation–contraction coupling in the heart ventricle. T3+Dex enhanced elementary Ca release measured by Ca sparks and promoted RyR2 (ryanodine receptor) structural organization. Simultaneous measurements of L-type Ca current and intracellular Ca release confirmed enhanced functional coupling between L-type Ca channels and RyR2 in T3+Dex-treated cells. Conclusions: : Our results suggest a permissive role of combined thyroid and glucocorticoid hormones during the cardiac differentiation process, which when coupled with further maturation on Matrigel mattress, is sufficient for T-tubule development, enhanced Ca-induced Ca release, and more ventricular-like excitation–contraction coupling. This new hormone maturation method could advance the use of hiPSC-CM for disease modeling and cell-based therapy. Abstract : Supplemental Digital Content is available in the text.